The Task of the Cleric : Cartography, Translation, and Economics in Thirteenth-Century Iberia - Pinet, Simone (Book collections on Project MUSE., 2016)
"Composed in early thirteenth-century Iberia, the Libro de Alexandre was Spain's first vernacular version of the Romance of Alexander and the first poem in the corpus now known as the mester de clerecía. These learned works, written by clergy and connected with both school and court, were also tools for the articulation of sovereignty in an era of prolonged military and political expansion. In The Task of the Cleric, Simone Pinet considers the composition of the Libro de Alexandre in the context of cartography, political economy, and translation. Her discussion sheds light on how clerics perceived themselves and on the connections between literature and these other activities. Drawing on an extensive collection of early cartographic materials, much of it rarely considered in conjunction with the romance, Pinet offers an original and insightful view of the mester de clerecía and the changing role of knowledge and the clergy in thirteenth-century Iberia."--